Characterization in Ahmad Fuadi’s Novel Negeri 5 Menara - Ningsih, D W (KnE Social Sciences, 2018)
This study analyzes the characters’ characterization in Negeri 5 Menara, a novel written by A. Fuadi. The purpose of this study is to find out the characterization of the protagonis found in the novel. analyzes the intrinsic elements as the supporting elements in analyzing the characters’ characterization: Good and Bad Characters as Good prejudice, honesty, respecting people, friendship, insincerity, and jealousy. The result of this study is that there is a correlation between the characterization of the character and the intrinsic elements in the Negeri 5 Menara according to the theme and message, the plot and plotting as well as the characters’ characterization in the story. The theory used in this study is proposed by Nurgiyantoro (2012) and the method used in analyzing the problems is proposed by Creswell (2009). Keywords: character, characterization, intrinsic elements